Selection and Training of Flight Instructors (Texas Journal of Multidisciplinary Studies, 2022)
This article discusses the features of improving the skills of selection and training of flight instructors, as well as the features of preparing future pilot-engineers for the profession of a pilot, shortcomings and ways to overcome them in practical flights.